Demand for School Quality and Local District Administration. (June 2022) - Collins, Courtney A.; Kaplan, Erin K.
Abstract: In 2013 Memphis City Schools and Shelby County Schools consolidated into a unified system, creating one of the largest districts in the nation. Six Memphis suburbs subsequently voted to create separate municipal districts. Many complex school zoning changes resulted from the merger and subsequent splintering of districts. This provides a rare opportunity to identify how the value of academic quality and local district control are capitalized in housing prices, independent of school-level demographic characteristics. Using a difference-in-differences approach including a repeat sales specification, we find that a one standard deviation increase in test scores increases housing prices by 2-3%, while district administration accounts for 6-8% of home values. We also consider the effect of student demographics and find that school-level diversity has a negative impact on home values, independent of academic performance and district administration.